Biomass‐Derived Activated Carbon Nanoarchitectonics with Hibiscus Flowers for High‐Performance Supercapacitor Electrode Applications - Yan, Dong; Liu, Lu; Wang, Xingyan; Xu, Ke; Zhong, Jinghan (Chemical engineering & technology, 2022)
Activated carbon is the most widely used electrode material in electrochemical double‐layer capacitors. The rational utilization of biomass energy waste to prepare porous carbon supercapacitor electrodes has effectively realized both the use of biomass waste and the industrial production of high‐performance supercapacitor electrodes. A simple method to employ roselle waste as the precursor of porous carbon supercapacitor electrodes is described. Electrochemical characterization confirmed that an electric double layer with high specific capacitance was formed in the system. The HCF‐3 supercapacitor electrode proved to have good cycle stability. Roselle‐based porous carbon has great potential as a low‐cost, environmentally friendly, and high‐efficiency supercapacitor electrode material. Biomass‐derived activated carbon nanoarchitectonics with hibiscus flowers is prepared by employing a two‐step process involving carbonization and KOH chemical activation. Hibiscus flowers‐derived activated carbon exhibits excellent electrochemical properties when used as supercapacitor electrodes and may promote the large‐scale application of three‐dimensional porous carbons in energy storage.